2019
DOI: 10.5114/hm.2020.88148
|View full text |Cite
|
Sign up to set email alerts
|

Drops in physical performance during intermittent small-sided and conditioned games in professional soccer players

Abstract: Purpose. The purpose of this study was to identify variations in external load measures between sets (3 × 4'/2' rest) of small-sided and conditioned game formats (goalkeeper + 5 vs. 5 + goalkeeper with specific tactical demands). Methods. Overall, 10 male professional soccer players (age: 28.1 ± 3.8 years, experience: 7.9 ± 2.9 years, height: 180.3 ± 5.8 cm, weight: 76.5 ± 6.3 kg) from a team competing in the first Portuguese league and in the UEFA Europa league participated in the study. Distance covered, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
4
5
0
Order By: Relevance
“…Trivial changes were observed within intervals in almost all cases. This is in agreement with recent studies reporting trivial to small changes in the second interval [ 25 , 26 , 33 ]. Dellal et al [ 25 ] showed a significant reduction from the first to fourth intervals (but not from the first to second intervals) in high- and very high -intensity activities (~-26; -37%).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Trivial changes were observed within intervals in almost all cases. This is in agreement with recent studies reporting trivial to small changes in the second interval [ 25 , 26 , 33 ]. Dellal et al [ 25 ] showed a significant reduction from the first to fourth intervals (but not from the first to second intervals) in high- and very high -intensity activities (~-26; -37%).…”
Section: Discussionsupporting
confidence: 94%
“…The reductions that do occur during SSGs are likely influenced primarily by other factors, such as training regimens compared to the interval set number per se . For instance, Clemente et al [ 26 ] examined variations in external load within different intermittent regimens (6 × 3 min and 3 × 6 min). They found that longer intervals contribute to more substantial decreases in total distance, running distance, and total values of accelerations and decelerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic nature of soccer implies intra-and inter-individual variability [5,6] in terms of the physical demands imposed during training sessions, mainly considering that a significant part of training is based on game-related drills (e.g., positioning games, smallsided games, full-sized games) [7][8][9]. This variability can be explained by contextual factors such as opponent level, score status, or the half or period of the games [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…internal (e.g., rating of perceived exertion [RPE], visual analogue scale [VAS]) and external (e.g., total distance covered, accelerations/decelerations) load measures are fundamental to elicit peak performance and reduce the risk of injury over the season [13][14][15][16][17][18]. However, the effects of biological maturity on the training load have not been fully investigated in youth soccer.…”
Section: Introductionmentioning
confidence: 99%